Structural flexural strengthening through material bonded to the concrete substrate - Victor Hugo Dalosto de Oliveira; Rodolfo Alves Carvalho; Rodolfo Rabelo Neves; Luana Ferreira Borges; Paulo Chaves de Rezende Martins; Marcos Honorato de Oliveira; João Paulo de Almeida Siqueira; Rafael de Almeida Sobral; Sidney Luan Teixeira de Nazaré; Carlos Henrique de Moura Cunhac (Acta Polytechnica CTU Proceedings)
This article proposes an alternative method for the structural design of reinforced concrete elements strengthened in bending by metallic plates or fiber-reinforced polymer (FRP) bonded to the concrete substrate. It is proposed a new calculation procedure for the strengthening using thin adhered material bonded to the element surface that dispenses the iterative process generally used in the design. The proposed routine is validated by comparison with other methods. A practical example is also presented, applying the procedure to an element of a building where a load change was foreseen. As result, it was verified that the proposed procedure provides values similar to the trial-and-error method used in the FRP strengthening design. Results are also coherent with other methods available in the literature for metallic plates. Therefore, since this routine obtains similar values without using an iterative method, its applicability in the design becomes advantageous.